Performance and serum parameters of growing pigs fed semi-purified glycerin - Verussa, Guiomar H.; Corassa, Anderson; Pina, Douglas S.; Ton, Ana P. S.; Komiyama, Cláudia M.; Teixeira, Alexandre O. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: the use of semi-purified glycerin in pig diets has been studied as an alternative energy source. Objective: to evaluate growth performance and serum levels of glucose, triglycerides, cholesterol, and urea in pigs fed diets containing semi-purified glycerin during the growth phase. Methods: forty barrows with an initial weight of 27.30 ± 1.74 Kg, distributed in a randomized complete block design with four treatments and five replicates were used. The dietary treatments were a combination of corn and soybean meal diets with the addition of 0, 5, 10 or 15% semi-purified glycerin. The experimental period lasted 27 days and was divided into two periods. Results: during Period 1, pig performance did not differ with the inclusion of semi-purified glycerin in the diet. In Period 2, an improvement in average daily weight gain was observed. In the total period, an improvement was observed in the average daily weight gain, feed/gain ratio and final weight of the animals. However, serum parameters were not affected by the inclusion of semi-purified glycerin in the diets. Conclusion: the addition of up to 15% semi-purified glycerin to the diet of growing pigs improves growth performance without affecting serum parameters.